2005
DOI: 10.1213/01.ane.0000160585.43587.5b
|View full text |Cite
|
Sign up to set email alerts
|

Revising a Dogma: Ketamine for Patients with Neurological Injury?

Abstract: Ketamine can be used safely in neurologically impaired patients under conditions of controlled ventilation, coadministration of a {gamma}-aminobutyric acid receptor agonist, and avoidance of nitrous oxide. Its beneficial circulatory effects and preclinical data demonstrating neuroprotection merit further animal and patient investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(142 citation statements)
references
References 97 publications
1
137
0
4
Order By: Relevance
“…Ketamine is a parenteral anesthetic that non-competitively blocks the NMDA receptor [9] . It has been shown that ketamine protects various tissues from I/R injury, such as brain [10] , myocardium [11] and skeletal muscle [12] . To the best of our knowledge, no previous studies have evaluated the effects of ketamine on intestinal motility impairment and tissue damage induced by I/R.…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine is a parenteral anesthetic that non-competitively blocks the NMDA receptor [9] . It has been shown that ketamine protects various tissues from I/R injury, such as brain [10] , myocardium [11] and skeletal muscle [12] . To the best of our knowledge, no previous studies have evaluated the effects of ketamine on intestinal motility impairment and tissue damage induced by I/R.…”
Section: Introductionmentioning
confidence: 99%
“…Under appropriate sedation with controlled ventilation conditions, ketamine does not increase ICP, however, when given at 2 mg/kg or above in awake children and adults, it increases ICP and, especially, if there is high ICP this increase is more pronounced. These patients have effective respiration as ETCO 2 and arterial CO2 do not increase and it is stated that nearly all have obstructed ventricular system (due to no shunt or shunt not working) (4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Initial early ketamine literature did report an increase intracranial pressure (47). A more recent literature review challenges these early reports and suggests a possible neuroprotective role for ketamine (55).…”
Section: Ketaminementioning
confidence: 99%